2017
DOI: 10.1098/rsif.2017.0372
|View full text |Cite
|
Sign up to set email alerts
|

The power–speed relationship is U-shaped in two free-flying hawkmoths (Manducasexta)

Abstract: A flying animal can minimize its energy consumption by choosing an optimal flight speed depending on the task at hand. Choice of flight speed can be predicted by modelling the aerodynamic power required for flight, and this tool has previously been used extensively in bird migration research. For insects, however, it is uncertain whether any of the commonly used power models are useful, as insects often operate in a very different flow regime from vertebrates. To investigate this, we measured aerodynamic power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…The difference between the two P total values represents the maximum energetic benefit of elastic energy exchange. Using this general strategy in Manduca sexta but with different experimental approaches, Willmott & Ellington (blade element models), Sun & Du (computational fluid dynamics), and Warfvinge et al (particle image velocimetry) concluded that elastic energy exchange can reduce P total by up to 20 -35% [8,7,9]. To extend upon this work, Dickinson & Lighton utilized respirometric measurements combined with model based estimates of P aero and P inertial [5].…”
Section: Thoracic Exoskeleton Returns the Maximum Amount Of Beneficiamentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between the two P total values represents the maximum energetic benefit of elastic energy exchange. Using this general strategy in Manduca sexta but with different experimental approaches, Willmott & Ellington (blade element models), Sun & Du (computational fluid dynamics), and Warfvinge et al (particle image velocimetry) concluded that elastic energy exchange can reduce P total by up to 20 -35% [8,7,9]. To extend upon this work, Dickinson & Lighton utilized respirometric measurements combined with model based estimates of P aero and P inertial [5].…”
Section: Thoracic Exoskeleton Returns the Maximum Amount Of Beneficiamentioning
confidence: 99%
“…In this case, all excess inertial power (P inertial − P aero ) is stored in spring-like structures and returned to reduce P inertial for the subsequent half stroke [4,5]. Several modeling and indirect mechanical measures have estimated the potential benefits of elastic energy exchange afforded by the thorax and muscles during flight [6,7,8,9]. Blade element models, computational fluid dynamics, and tomographic particle image velocimetry estimates suggest that perfect elastic energy exchange could reduce P total by up to 20 -35% in Manduca sexta [8,9,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a modified version [38] of the method proposed by von Busse et al [7], in which Helmholtz-Hodge decomposition was used to infer the velocity fields beyond the measurement plane (to the cross-sectional limits of the wind tunnel, which was assumed to be a square with 1.2 m sides) based on the vorticity in the measurement area. Although the air outside the immediate wake is not accelerated to high speeds, the volume of this air is large and an extension of the vector field was necessary to capture all the added kinetic energy [7] (electronic supplementary material, figure S8).…”
Section: Powermentioning
confidence: 99%
“…The actual velocities in the masked measurement area were kept for the analysis. The average kinetic energy added to the wake (E wb ) during a wing beat was calculated by summing the kinetic energy over a fixed number of wingbeats, and subsequently dividing by the number of wingbeats [38]:…”
Section: Powermentioning
confidence: 99%